Pengaruh Akses Informasi Terintegrasi dan Layanan Pelanggan Terintegrasi Terhadap Kepuasan Pelanggan Toko Buku Gramedia Di Kota Palembang (Studi Pada Mahasiswa Fakultas Ekonomi Universitas Sriwijaya) - Cut Anggi Sari; Dessy Yunita; Zakaria Wahab (JEMBATAN, 2022)
This study aims to determine the impact of integrated information access and integrated customer service on customer satisfaction at Gramedia bookstores in Palembang, both simultaneously and partially. This study used primary data collected through a questionnaire from a sample of 100 respondents. The analytical techniques used are the F test, the T test, and the multiple linear regression analysis. The F test showed a significant value of 0.000, meaning that the independent variables, namely integrated information access and integrated customer service, simultaneously had a positive and significant impact on customer satisfaction at Gramedia bookstores in Palembang. Partially, integrated information access (X1) had a positive and significant impact on customer satisfaction (Y), as well as integrated customer service (X2) had a positive and significant impact on customer satisfaction (Y).